Prevalência de insuficiência/deficiência de vitamina D e fatores associados em adolescentes escolares - Araújo, Eduarda Pontes dos Santos (2016)
Introduction: Vitamin D has important functions in bone metabolism and in the pathophysiology of various chronic diseases. Vitamin D deficiency has been reported worldwide and several determinants may be related to this phenomenon. Objective: To estimate the prevalence and factors associated with vitamin D deficiency / deficiency in school adolescents from a capital city in the northeast region of Brazil. Methodology: This was a cross-sectional epidemiological study in adolescents aged 15 to 19 from public schools in Joao Pessoa-PB / Brazil. Serum levels of 25 (OH) D were measured by blood samples. Sociodemographic and behavioral data were obtained through a semistructured questionnaire, where they were included in the independent variables: sex, skin color, social benefits, mother's schooling, hours of sleep per day, daily solar exposition, physical activity exposed to the sun, Activity or physical inactivity, food consumption, nutritional status and biochemical analyzes of calcium and serum PTH. The nutritional status was evaluated according to the recommendations of the WHO (World Health Organization). The analysis of factors associated with vitamin D deficiency was performed by simple and multivariate Poisson Regression. Results: The prevalence of 25 (OH) D deficiency / deficiency was 57.3%, with the female population showing a higher prevalence (p = 0.000) than the male sex. In no analyzed variables, the female sex presented average vitamin D levels higher than 30 ng / dL (reference value). After the categorization of the sample by sex, in the final model, the nutritional status (RP: 2.78, p = 0.006) was associated with 25 (OH) D deficiency / deficiency in male adolescents and serum calcium (RP: 1 , 32, p = 0.018) in females. Conclusion: Data from the present study estimate a high prevalence of vitamin D deficiency / deficiency in a population of school adolescents in northeastern Brazil, especially females, and the associated factors were different among the groups analyzed. The data from the study suggest that strategies such as obligatory fortification in food sources of vitamin D and the possible supplementation of individuals in adolescence, especially in the female sex, are considered by the public health organizations of Brazil and the World.